Chronicles of the force - Bray, Adam; Fentiman, David; Horton, Cole (New York, New York DK Publishing, 2016)
This up-to-date companion to LEGO "Star Wars," contains detailed information about the latest sets and minifigures and is illustrated with extensive photography.--
Encyclopedia
Includes index
Ages 6+
1
Keywords: LEGO toys -- Juvenile literature; LEGO toys; Star Wars figures -- Juvenile literature; Star Wars figures; LEGO toys; Star Wars figures; Juvenile works